PENGAMANAN IMAGE DENGAN MODIFIKASI ALGORITMA ELECTRONIC CODE BOOK (ECB) - Asti, Melinda; Kamsyakawuni, Ahmad; Santoso, Kiswara Agung (Jurusan Matematika FMIPA Universitas Jember, 2018)
Cryptography is knowledge of encoding data to ensure the confidentiality, security, validity and integrity of data. Cryptography is divided into two namely classical cryptography and modern cryptography. One example of modern cryptography is the Electronic Code Book (ECB). Electronic Code Book (ECB) is a modern cryptographic method used to encrypt and decrypt text, images and more. The image is formed from several pixels which consist of several bits in a pixel. Bits are divided into two namely Least Significant Bit (LSB) and Most Significant Bit (MSB).LSB is the four rightmost bits while MSB is the leftmost four bits of a pixel. The purpose of this study is to compare the level of security of Electronic Code Book (ECB) image security results with the results of securing an Electronic Code Book (ECB) modified image. The data used in this study are 8 RGB and Greyscale images also a key in the form of one ASCII character. The results obtained show that securing images with modified Electronic Code Book (ECB) is safer than securing images with Electronic Code Book (ECB) based on histogram analysis, differential analysis and correlation coefficients. Keywords: ASCII, Electronic Code Book (ECB), Most Significant Bit (MSB)